PHARMACEUTICAL STANDARDIZATION OF KANYALOHADI VATI - Rajam, *Sireesha; Sridurga, Ch (International Journal of Ayurveda and Pharma Research, 2018)
Rasa oushadies are the potent Ayurvedic preparations mainly containing metals and minerals. These oushadies possess a wide range of therapeutic efficacy and are considered superior because of their qualities like small dose, quick action, palatability and longer shelf life. Kanyalohadi Vati is an important Rasaoushadi described in Rasa Tantra Sara Va Siddha Prayoga Sangraha indicated for the management of the diseases Anartava, Kashtartava and Aniyamithartava. The ingredients present in the “Kanyalohadi vati” are Kaseesa Bhasma, Elua (Musambaram), Twak, Ela, Sunthi and Gulkand. The main pharmaceutical procedures involved in the preparation of Kanyalohadi Vati are Shodhana, Bhavana, Marana, Elua nirmana, Gulkand nirmana, Churna nirmana and preparation of Kanyalohadi Vati. The specific pharmaceutical blend of these contents can result in a more effective formulation. Therefore the present study has been planned to standardize the method of preparation of Kanyalohadi Vati according to the method explained in the classical literature.